Non-Invasive Temperature Measurement and Control Techniques under Thermo-Mechanical Fatigue Loading - Robert Lancaster (Materials Science and Technology, 2014)
A non-invasive temperature measurement, control and profiling technique has been investigated for use with thermomechanical fatigue loading. The technique utilises an infrared thermography camera and Rolls–Royce developed thermal paint to control and monitor cyclic temperature. Thermal paint is used to maintain a stable surface emissivity upon the test piece. The accuracy of the technique is compared against type N thermocouples and a pyrometer for both temperature control and monitoring purposes. Diverse test specimen geometries and alloy compositions are used over a 100–700°C temperature range. Effects on temperature measurement accuracy such as thermocouple shadowing are highlighted and quantified. The non-invasive technique has proved accurate to within ±2°C of the reference thermocouples when in combination with the thermal paint coating.